Thymoma and pure red cell aplasia with hypoplasia of megakaryocytopoiesis: A rare and life-treating condition. (April 2020) - Lo Iacono, Giorgio; Gigli, Federica; Gherzi, Lorenzo; Avenoso, Daniele; Fiori, Stefano; Sedda, Giulia; Tarella, Corrado; Spaggiari, Lorenzo
Abstract: Thymic tumors are rare diseases with an incidence of 0.15 cases per 100, 000 person-years. They can be associated with a variety of other syndromes, such as Myasthenia Gravis or autoimmune disorders. Among them, pure red cell aplasia is a hemato-pathological condition characterized by anemia, reticulocytopenia and erythroid cell hypoplasia of bone marrow. Here, we reported a case of a 62-year-old female with a long history of neurologic symptoms due to Myasthenia Gravis. She was diagnosed with thymoma, with mediastinal mass and pleural thickening. After chemoradiotherapy treatment, she was surgically resected successfully, but she developed anemia and severe thrombocytopenia, worsening in respiratory failure requiring intubation. A bone marrow biopsy was performed resulting in a red-cell aplasia with marked hypoplasia of megakaryocytopoiesis compatible with pure red cell aplasia with acquired thrombocytopenia. Considering that there are no standard treatments, clinical condition improvement was achieved only after some lines of medical treatment. Our data, together with the few already published, help to raise the attention towards acquired cytopenias and the need to optimize the treatment for a potentially life-threatening condition.